New porphyrin dendrimers with fluorenyl-based connectors: a simple way to improving the optical properties over dendrimers featuring 1, 3, 5-phenylene connectors. (26th February 2020) - Zhang, Xu; Ben Hassine, Sarra; Richy, Nicolas; Mongin, Olivier; Blanchard-Desce, Mireille; Paul, Frédéric; Paul-Roth, Christine O.
Abstract : Dendrimers with new fluorenyl-based connectors have been synthesized and characterized. Their detailed luminescence properties and selected photophysical properties are discussed in the frame of two-photon-induced theranostics. Abstract : Two new meso -tetrafluorenylporphyrin-cored dendrimers 1 and 2 have been synthesized and characterized. The peripheral fluorenyl units of these dendrimers are linked to the central tetrafluorenylporphyrin (TFP ) core by original fluorene-based connectors instead of the more classic 1, 3, 5-phenylene unit. Selected linear and non-linear optical (LO and NLO) properties were determined for these dendrimers via absorption or emission studies and by two-photon excited fluorescence (TPEF) measurements. Dendrimer 1, which has a conjugated and quite rigid structure, exhibits a significantly higher two-photon absorption (2PA) cross-section than dendrimer 2, presenting a non-conjugated and more flexible structure, as well as better luminescence and singlet oxygen activation quantum yields. Both dendrimers exhibit higher 2PA cross-sections than several closely related TFP -based dendrimers previously characterized. However, among them, dendrimer 1 is the only one outperforming all these compounds in terms of 2PA brightness and 2PA oxygen sensitization. Thus, the new type of connector (or dendrimeric node) introduced in 1 appears to be quite appealing for the design of photosensitizers aimed at theranostic uses in the future.